Pengaruh Kualitas Pelayanan, Fasilitas dan Lokasi Terhadap Keputusan Menginap di Travelodge Hotel Batam - Rimayang Anggun Laras Prastianty Ramli; Indah Nur Agustiani; Rudi Yanto Batara Silalahi (STIEPAR YAPARI Bandung, 2021)
This study aims to determine the effect of service quality, facilities and location on the decision to stay at Travelodge Hotel Batam. This research was conducted with a survey approach consisting of variables of service quality (X1), facilities (X2), location (X3) and decision to stay (Y). The sample used in this study amounted to 97 respondents. Statements were given using a questionnaire distributed through Random Sampling technique and the data analysis methods used were validity test, reliability test, classical assumption test,. The data collected through the questionnaire was processed using the application of the Statistical Product and Service Solution (SPSS) version 20 program. The test results are (1). The service quality variable has a positive and significant effect on the stay decision variable where the significance level is 0.000 < 0.05, (2). Facilities have no positive and significant effect on the decision to stay where the significance level is 0.822 > 0.05, (3). Location has a positive and significant effect on the decision to stay where the significance level is 0.000 < 0.05, (4). Quality of service, facilities, simultaneously have a positive and significant effect on the decision to stay where the significance level is 0.000 <0.05.